The impact of quranic recitations on moral and social objectives - Zayd Thabit Abdulrahman,; Mohd Faizulamri Mohd Saad,; Sabri Mohamad, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The objective of this research is to investigate the maqasid (objectives) perspective with regards to the influence of Quranic recitations in terms of their authenticity, which were revealed by Allah Almighty to serve as a maqasid approach to guide individuals in all aspects of life. In Islam, the social and moral virtues hold a significant position as they are integral to the rules and instructions of the religion. The Islamic faith advocates for individuals to actively pursue and uphold social and moral obligations, while promoting virtuous conduct and discouraging any form of dishonorable behavior. This serves to foster the development of communities that embody these exceptional human qualities. The present study employed descriptive and analytical methodology. The primary data sources for the study were scholarly articles and books, which were thoroughly documented and subjected to rigorous analysis. The study conducted a content analysis that involved a systematic evaluation of Quranic recitations with the aim of achieving a comprehensive understanding of the interpretation of the Quran. This was done by considering the maqasid and the method of recitation (articulation of Quranic verses) in order to address societal issues. The finding revealed that the Quranic recitations were regarded as a reliable basis for Islamic rules. The aforementioned findings were derived through the process of inferring the maqasid and impact of the Quran on some Islamic rules. The significance of genuineness in both worship and professional endeavors can be seen by the objectives and impacts involved. The results of the study revealed that Quranic recitations have impacts on social objectives by emphasizing the importance of verification and assurance in public affairs and various life situations.